Solution-Focused Brief Counseling: An Effective Strategy for Reducing Anxiety During School Exams - Wahyudin, Herul; Ramli, M.; Chusniyah, Tutut; Eva, Nur; Oktasari, Maria (Edu Consilium : Jurnal Bimbingan dan Konseling Pendidikan Islam, 2024)
This study explores the effectiveness of brief solution-focused counseling (SFBC) in reducing exam anxiety in students. Exam anxiety is one of the factors that can interfere with students' mental health and academic performance. SFBC, as a solution- and outcome-oriented approach, relies on students' internal and external resources and has been proven effective in the school context. Through techniques such as problem-free talk, magic questions, scaling questions, exclusion questions, marking minefields, and formulaic first session tasks, this study aims to identify strategies that can reduce students' exam anxiety. The method used is Systematic Literature Review (SLR) to determine the effectiveness of using SFBC in reducing students' exam anxiety. The results showed that SFBC is effective in reducing students' exam anxiety by emphasizing the development of counseling strengths and resources. The conclusion of this study is that SFBC is an efficient and effective therapeutic approach to help reduce student exam anxiety.